A method for estimating the vehicle impact speed in collision with stationary vehicle or barrier using camera video record - Myung-Cheol Park; Jong-hyuk Kim; Won-taek Oh; Sang-hyun Iim; Seong-Jin Kim; Woo-Jeong Jeon (Forensic Science International: Reports, 2024)
In Korea, most drivers equip their vehicles with a black box camera, used to estimate the speed of the vehicle in case of traffic accidents such as car-to-car collisions, single-car accidents, and car-to-pedestrian accidents. Traditionally, speed estimation using the camera video has been done by using the distance between the road lane, surrounding structures, etc.However, when the following vehicle collides with a stationary leading vehicle or barrier, and no road lanes or structures are visible around the driving path in the black box camera video of the following vehicle, the speed of the following vehicle could be just estimated according the deformations on the collided vehicles or objects.Therefore, in this study, when a vehicle collision occurs, a virtual parallel line is drawn between the leading vehicle and the following vehicle in the black box camera image of the following vehicle and analyzed geometrically to estimate the distance and the speed of the following vehicle.After the vehicle collision experiment, the speed was estimated using the method proposed in this study using the captured black box video. As a result, it was confirmed that the accuracy was high when the collision speed was low. So The method proposed in this study is expected to be used to estimate collision speed in the cases of low impact speed in the rear end collisions.